Mixed lagrange time delay estimation autoregressive Wiener filter application for real-time SEM image enhancement - Sim, K.S.; Law, K.K.; Tso, C.P. (WILEY-LISS, 2007)
A new filter is developed for the enhancement of scanning electron microscope (SEM) images. A mixed La mange time delay estimation auto-regression (MLTDEAR)-based interpo lator is used to provide an estimate of noise variance to a standard Wiener filter. A variety of images are captured and the performance of the filter is shown to surpass the conventional noise filters. As all the information required for processing is extracted from a single image, this method is not constrained by image registration requirements and thus can be applied in real-time in cases where specimen drift is presented in the SEM image.